Period formula for RC frame buildings considering infill wall thickness and elasticity modulus - Kocak, A.; Borekci, M.; Zengin, B. (ELSEVIER SCIENCE BV, 2018)
Estimation of a proper fundamental vibration period is an important issue in the process of the design and/or evaluation of a building. Mostly, infill walls are assumed as nonstructural element and ignored in the estimation of the vibration period of a building in terms of stiffness. However, studies showed that infill wall has significant effect on vibration period and should be considered in the estimation of period. Even some proposed equations take into account infill walls in the estimation of period, they do not consider changing of the stiffness of infill walls. In this study, an empirical equation is proposed as a function of building height, elasticity modulus of infill wall and infill wall thickness. For this purpose, building periods were determined with considering different infill wall elasticity modulus, infill wall thicknesses (thus different infill wall stiffness) and building heights. Nonlinear regression analyses were conducted with a comprehensive statistical study. Effect of infill wall elasticity modulus and thickness on vibration period was investigated. Finally, comparisons of proposed equation of this study and previous studies were conducted. (C) 2018 Sharif University of Technology. All rights reserved.
Keywords: Period; Infill wall thickness; Infill wall elasticity modulus; RC structures; Modal analysis; REINFORCED-CONCRETE BUILDINGS; FUNDAMENTAL PERIODS; VIBRATION; HEIGHT; Engineering